A cross-national and cross-cultural approach to global market segmentation : an application using consumers' perceived service quality - Malhotra, Naresh K. (2013)
The spread of global culture is being facilitated by the proliferation of transnational corporations, the rise of global capitalism, widespread aspiration for material possessions, and the homogenization of global consumption. The extent of convergence of cultural values across nations has been debated by international marketing researchers. However, from a practical standpoint, transnational firms require a cross-national, cross-cultural approach to market segmentation that can be used to guide the development of global marketing strategies. In this study, the authors investigate the application of cross-national versus cross-cultural approaches to market segmentation through a rigorous empirical investigation in the context of banking services. Although services constitute the fastest growing sector of the world economy, few studies have examined global market segmentation strategies for them. The authors develop theory-based cross-national hypotheses and test them by estimating a structural model of consumers' perceived service quality using survey data from two countries: the United States and India. They test cross-cultural hypotheses by estimating the same model on culture-based clusters. They demonstrate that there are distinctive differences between cross-national and cross-cultural models of perceived service quality and highlight the growing relevance of cross-cultural research approaches. More generally, the cross-national, cross-cultural approach to market segmentation can guide the development of global marketing strategies for services and improve business performance.